1991
DOI: 10.1111/j.1600-051x.1991.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of proximal plaque removal using floss and interdental brushes

Abstract: The removal of interproximal plaque was compared using a standard toothbrush alone, a toothbrush with unwaxed dental floss and a toothbrush with an interdental brush. 30 previously treated periodontal patients were given the cleaning aids in a three-way crossover study design. After each 1 month trial period, scores for gingivitis, buccal/lingual plaque and proximal plaque were recorded. Mean GI scores for subjects were 0.37 using the toothbrush only, 0.36 using the toothbrush with floss and 0.32 using the too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 12 publications
4
74
0
7
Order By: Relevance
“…It is unable to reach the gums underneath the wires; therefore, compliance with dental floss is low for orthodontic patients. In recent studies comparing floss and interdental brush, improved interproximal plaque reduction was shown in the interdental brush group [24][25][26]. It was also reported that the use of interdental brushes was more effective in the removal of plaque and resulted in a larger reduction of probing depth than the use of dental floss [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is unable to reach the gums underneath the wires; therefore, compliance with dental floss is low for orthodontic patients. In recent studies comparing floss and interdental brush, improved interproximal plaque reduction was shown in the interdental brush group [24][25][26]. It was also reported that the use of interdental brushes was more effective in the removal of plaque and resulted in a larger reduction of probing depth than the use of dental floss [27].…”
Section: Discussionmentioning
confidence: 99%
“…6,9,11,12 Tüm avantajlarının yanı sıra, dikkatli kullanılmadığında metal gövdenin diş ve kök yüzeyinde travma oluşturması nedeniyle dentin hassasiyetini tetikleme ve interdental papilin zedelenmesi gibi dezavantajları da mevcuttur. 3,13 Bu sebeple üreticiler, kullanım kolaylığı sağlamak amacıyla metal içermeyen esnek gövdeli plastik ara yüz temizleyici araçları piyasaya sunmuşlardır.…”
unclassified
“…One additional study was gleaned from the reference list, for a total of 9 studies included in this systematic review. [1][2][3][4][5][6][7][8][9] Both randomized controlled clinical trails and controlled clinical trials were selected for review; however, considerable heterogeneity was observed in the 9 studies related to study design, number, gender and age of participants, and outcome variables.…”
mentioning
confidence: 99%